Prostitution: You can’t have your cake and sell it - Chevarie-Cossette, S (University of Oxford, Oxford Uehiro Centre for Practical Ethics, 2017)
I offer an unorthodox argument for the thesis that prostitution is not just a normal job. It has the advantage of being compatible with the claim that humans should have full authority over their sexual life. In fact, it is ultimately the emphasis on this authority that leads the thesis that prostitution is a normal job to collapse. Here is the argument: merchants cannot (both legally and morally) discriminate whom they transact with on the basis of factors like the ethnicity or the religion of their client; but if prostitutes are ‘sex merchants’, then they cannot (both legally and morally) discriminate whom they have sex with on the basis of these factors. Yet everyone should have the full discretionary power to refuse to have sex under any circumstances.